Customer Loyalty Analysis Affected by Location and Promotion through Purchase Decisions and Customer Satisfaction - Azka Nur Khanifah; Aris Budiono (Yayasan Ilomata, 2022)
ABSTRACT: This study aims to analyze customer loyalty which is influenced by location and promotion through purchasing decisions and customer satisfaction made by visitors to Indomaret Cipinnag Indah. Data obtained in April 2022 as many as 130 respondents. Thirty respondents for validity and reliability testing and 100 respondents were used for path analysis testing to know the direct and indirect effects of the dependent variable on the independent variable. Sampling using the Roscoe technique, all of whom are visitors to Indomaret Cipinang Indah. This study's results indicate that location significantly affects purchasing decisions, customer satisfaction, and customer loyalty. The promotion affects purchasing decisions but does not affect customer satisfaction and loyalty. Purchase decisions affect consumer loyalty. Consumer Satisfaction does not affect consumer loyalty. Indirectly location and promotion affect consumer loyalty through purchasing decisions and do not affect customer satisfaction.